Concealing social responsibility? Investigating the relationship between CSR, earnings management and the effect of industry through quantitative analysis - Lars Moratis; Max van Egmond (International Journal of Corporate Social Responsibility (JCSR), 2018)
The relationship between corporate social responsibility (CSR) and earnings management (EM) has only emerged recently as a topic of academic research. Literature suggests that firms may strategically use CSR to compensate for EM or to deflect stakeholder attention from EM. Studies on the EM-CSR relationships have so far yielded contradictory results. Additionally, research has largely neglected the influence of industry on this relationship. As scholars of both CSR and EM have suggested that industry effects may play a role, this study examines the relationship between the level of CSR performance of companies, the extent of EM firms are practising and the effect of industry (high vs. low environmental impact as a proxy for experienced stakeholder pressure). Using the Modified Jones model, discretionary accruals are estimated and used as a proxy for EM (accrual-based EM). Firm CSR performance is captured by using the Kinder, Lydenberg, Domino (KLD) database. Using a sample consisting of 5494 observations of US listed companies for the fiscal years 2003 until 2009, this study (1) finds no relationship between EM and CSR and (2) finds that the firms in the category high environmental impact do not seem to practice EM but do display higher levels of CSR performance. Finally, the article reflects critically on the concepts used in studying the EM-CSR relationship and its contribution to the literature.
Keywords: 650; Corporate social responsibility; Earnings management; Sustainability; Quantitative analysis; Modified Jones model; Discretionary accruals